INCREASING SKILLS WRITING TEXT SHORT STORIES USING PROBLEM POSING - Aurelia Sakti Yani; Dida Firmansyah (JLER (Journal of Language Education Research), 2018)
Writing is a skill that expresses or conveys ideas, one is able to write after reading many other writings, therefore it takes skill in writing short story text so that students are interested or persuaded for a learning process. A short story is a literary work which is a short story can be read once sitting, the method that researchers use in this research using problem posing approach. A problem-posing approach is an approach in which the child is invited to pose a problem or make a question of the existing text. This method is very suitable to use because it can make the students active in the class. This study aims to improve writing skills, especially vocational students. Therefore, it is expected in this method they have the freedom to express what is thought in the form of writing. If this approach is done continuously it will produce a work that is powerless and worthy to be read by audiences. With the problem-posing approach, the authors hope this research can improve the skills of writing short stories of students because through the approach of problem posing will make students insightful.